Meningkatkan Kemampuan Menulis Iklan Baris dan Sikap Kemandirian Menggunakan Media Iklan Kodek (Koran Lombok Post) pada Pembelajaran Berbasis Teks Kelas Viii SMPN 1 Selong Tahun 2018/2019 - Islahuddin, Islahuddin (SEBASA Jurnal Pendidikan Bahasa dan Sastra, 2019)
The purpose of this study was to improve the ability to write classified ads and attitudes of independence by using small advertisement media for class VIII students of SMPN 1 Selong in the learning year 2018/2019. This research is classroom action research (CAR) which consists of 2 cycles. Each cycle consists of 4 stages, namely 1) planning stage, 2) implementation, 3) Observation and reflection. The instrument of this research is in the form of tests and observation guidelines. The success of the action is determined by seeing an increase in the average value of the ability to write classified ads in cycle I to cycle II. The results showed an increase in the average value of writing classified ads in the first cycle of 75 to 81 in the second cycle, the score of the independent attitude 76 in the first cycle, to 88 in the second cycle. These results indicate that the use of codec advertisement media can improve the ability to write classified ads and independence in class VIII SMPN l Selong Academic Year 2018/2019.Keywords: writing, classified ads; independence; small advertising.